ANALISIS FAKTOR PENGHAMBAT MEMBACA PERMULAAN PADA SISWA KELAS I SD NEGERI SAWAH BESAR 01 SEMARANG - Andika Dwi Priyabada; Choirul Huda; Ladung Antoko (Jurnal Bionatural, 2024)
This study focuses on factors inhibiting beginning reading in class I B students at SD Negeri Sawah Besar 01 Semarang. The purpose of this study was to analyze the difficulties and factors inhibiting beginning reading in class I B students at SD Negeri Sawah Besar 01 Semarang. The research method used is descriptive qualitative. Data collection techniques used were observation, interviews, and documentation. Data analysis uses data reduction, data presentation, and conclusion. The research results show that the forms of difficulty and inhibiting factors faced by Class I B students at SD Negeri Sawah Besar 01 Semarang in the beginning reading are as follows. (1) Students are unable to recognize letters so students cannot sound them out, Students are unable to pronounce vowel and consonant letter sounds, Students do not understand and cannot read two words well, and Students are confused and unable to read the syllables in elementary level reading books. (2) factors that hinder students from beginning reading difficulties in Class I students at SD Negeri Sawah Besar 01 Semarang are internal factors and external factors. Internal factors include intellectual factors related to memory, motivation, and self-interest. External factors include family environmental factors which include the family's economic conditions, school factors which include teaching methods, and motivational factors from parents.